Dental Care among Secondary Level Students - Ban, Mina Kumari (Journal of Gurubaba, 2024)
This study entitled Dental care among secondly level students the study site of this study was Birendranagar municipality, Surkhet district. The main objectives of the study were to find out the knowledge on dental care, to find out existing practices on dental care and to assess dental problems of the respondents. This study was based on primary data as a descriptive type of research design and its nature was quantitative. All higher secondary schools' grade nine to ten students were population of the study. Altogether, 164 respondents were selected by the simple random sampling technique and lottery method. The primary data were collected through mainly interview schedule and observation sheet. After collecting data they were analyzed and interpreted in tables, charts and graphs using simple percentage. The study found that 62.19 percent of the respondents had the knowledge on dental care; brushing teeth eat nutritious food and regular checkup. Most of them were received information through media. Only few 12.80 percent had knowledge about fluoride. All (100 percent) respondents have knowledge of brushing teeth. Among them, 79.26 percent respondents had knowledge of teeth brushing twice in a day and rest of 18.90 percent had knowledge once in a day. Most (82.92 percent) respondent had known affect of not brushing teeth. Similarly, 67.07 percent respondents had known cause of dental caries. Here, 73.17 percent respondents agreed that smoking, chewing tobacco and nut affect on teeth. The respondents, 85.97 percent said that eat nutritious food is significant for healthy teeth. The study found that 50.60 percent respondents had dental caries, 17 percent respondents had dental plaque, and 4.6 percent had double (Dara) teeth and only 1.21 percent had black color teeth. The knowledge respondent on dental care was good and the practice levels of the respondents on dental care were satisfactory. This study was conducted among secondary level students only. Such studies should be conducted among educated and uneducated males as well as females too in various parts of the country.